2020
DOI: 10.2217/imt-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Severe Chronic Nonlichenoid Oral Mucositis in Pembrolizumab-Treated Patients: New Cases and a Review of the Literature

Abstract: Aim: To report of severe chronic oral mucositis (OM) in two pembrolizumab-treated cancer patients. Materials & methods: A retrospective chart review was performed. Inclusion/exclusion criteria detected patients that developed OM during pembrolizumab immunotherapy. In addition, we searched the literature for nonlichenoid OM in immunotherapy-treated cancer patients. Results: Two male patients treated for anaplastic astrocytoma and lung adenocarcinoma were included. Extensive painful OM (grade 4) dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previously, also reported a single palate SM in a patient using pembrolizumab. In both cases, the SMs emerged in inflammatory sites which are associated with oral reactions to immune checkpoint inhibitors (immune-related adverse events) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, also reported a single palate SM in a patient using pembrolizumab. In both cases, the SMs emerged in inflammatory sites which are associated with oral reactions to immune checkpoint inhibitors (immune-related adverse events) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the irAEs in terms of immediate effect on the ongoing cancer therapy, severity of symptoms, chronicity of the irAEs, and development of oral cancer were assessed. This paper does not include patients who were described by us in previous published works [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…The oral irAEs reportedly involve the oral mucosa and salivary glands [7,8], manifesting mainly as lichenoid and non-lichenoid lesions and salivary gland dysfunction, respectively [9][10][11]. Dysgeusia is reported sparsely, as well as anecdotal reports of medicationrelated osteonecrosis of the jaw and oral burning sensation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Amy et al reported severe chronic OM associated with pembrolizumab immunotherapy lasting for months even after the drug was stopped and representing the major cause of suffering and eating difficulties for cancer patients [28].…”
mentioning
confidence: 99%